2021
DOI: 10.3389/fpsyg.2021.734461
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Basic Psychological Need Satisfaction to Psychological Well-Being via Autonomous Motivation Among Older Adults: A Cross-Cultural Study in China and France

Abstract: According to self-determination theory (SDT), the satisfaction of the universal needs for autonomy, competence, and relatedness is important in order to enhance autonomous motivation, which in turn promotes psychological well-being (PWB), regardless of age or culture. In contrast, some cross-cultural perspectives challenge SDT's universalistic viewpoint, especially SDT's view that autonomy yields universal positive effects across Western and Eastern societies. To test these theoretical frameworks across cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 63 publications
(84 reference statements)
0
27
0
1
Order By: Relevance
“…In SDT (Deci & Ryan, 2000;Tang, Wang, & Guerrien, 2021), competence (effectance) as an innate motivational drive alludes to the propensity for mastery over one's endeavours, to have a positive effect on the environment and to attain valued outcomes within it. The innate psychological need for relatedness or belongingness points to the desire to care for others and to have a secure sense of belonging and connection to others in the social environment while also feeling supported and cared for by others (Deci et al, 2017;Tang et al, 2021). Autonomy reflects the psychological need for selfdetermination, that is, experiencing freedom, congruency, integration and volition in following personal interests and aspirations (Deci et al, 2017).…”
Section: The Intern Industrial Psychologist From a Self-determination...mentioning
confidence: 99%
See 2 more Smart Citations
“…In SDT (Deci & Ryan, 2000;Tang, Wang, & Guerrien, 2021), competence (effectance) as an innate motivational drive alludes to the propensity for mastery over one's endeavours, to have a positive effect on the environment and to attain valued outcomes within it. The innate psychological need for relatedness or belongingness points to the desire to care for others and to have a secure sense of belonging and connection to others in the social environment while also feeling supported and cared for by others (Deci et al, 2017;Tang et al, 2021). Autonomy reflects the psychological need for selfdetermination, that is, experiencing freedom, congruency, integration and volition in following personal interests and aspirations (Deci et al, 2017).…”
Section: The Intern Industrial Psychologist From a Self-determination...mentioning
confidence: 99%
“…Aspiring towards registering as a professional IP alludes to interns' sense of selfdetermined autonomous (extrinsic and intrinsic) motivation. Self-determination theory's notion of extrinsic motivation (Deci & Ryan, 2000;Tang et al, 2021) elucidates that the reason for pursuing a career as a professionally qualified IP is a http://www.sajip.co.za Open Access volitional (autonomous) decision derived from a belief in the personal importance or perceived value of the role and services in a social context. The notion of intrinsic motivation (Deci & Ryan, 2000;Tang et al, 2021) explains that IOP type of activities, roles and services are autonomously self-regulated and performed with interest, pleasure or satisfaction.…”
Section: The Intern Industrial Psychologist From a Self-determination...mentioning
confidence: 99%
See 1 more Smart Citation
“…personal growth, meaningful purpose in one’s life) well-being (Church et al, 2013 ). Another study conducted on the elderly in China and France found that satisfaction of autonomy was considered a basic psychological need which facilitated self-directed motivation, which was considered essential to psychological well-being by both elderly Chinese and French (Tang et al, 2021 ). Further empirical studies have shown that the self-determination theory (SDT), which postulates the importance of three basic psychological needs (i.e.…”
Section: Global/local and The East–west Dichotomymentioning
confidence: 99%
“…Further empirical studies have shown that the self-determination theory (SDT), which postulates the importance of three basic psychological needs (i.e. relatedness, autonomy, and competence) in promoting achievement and well-being, is generalizable and that autonomy, in particular, is equally important across east and west (Nalipay et al, 2020 ; Tang et al, 2021 ; Yu et al, 2018 ). The results of these studies have proven contrary to the beliefs of many cross-cultural researchers who cast doubt on the generalizability of certain values to non-western cultures.…”
Section: Global/local and The East–west Dichotomymentioning
confidence: 99%